Study of ACSR Conductor Characteristics on Power Losses and Voltage Drop in 500 kV Transmission Lines: A Case Study at Krian-Ungaran - Puji Slamet; Reza Sarwo Widagdo; Balok Hariadi (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
The transmission system is the stage of electricity distribution from the generator to the substation to the distribution system. During the process of distributing electric power, there is a voltage regulation that occurs whether it is still within safe limits or not because if it exceeds safe limits it can cause damage to electrical equipment. Power losses can occur due to several factors, namely insulator leaks, distance, and others. One of the issues identified is the use of ACSR (Aluminum Conductor Steel Reinforced) conductors, which, although commonly used due to their mechanical strength and relatively low cost, also contribute to significant power losses due to their resistance and susceptibility to environmental effects such as temperature rise. The transmission network in this study uses ACSR type conductor wire with a Dove type and a cross-sectional area of 327,77 mm² over a distance of 251 km, with a resistance value of 0.1024 Ω/km. The manual calculation method was employed by recording current and voltage values that change every day for one month. The conclusion obtained from manual calculations of power losses and voltage regulation is that the percentage of voltage regulation on transmission lines for one month remains within the safe limit, where the maximum allowed is 10 percent. However, despite the voltage being regulated within limits, significant power losses were recorded, with the highest loss being 16,79 MW and the lowest 6,01 MW. The total power losses on the transmission network for one month reached 272,92 MW, with an average of 9,09 MW per day. These findings highlight the drawback of using ACSR conductors in long-distance transmission lines, emphasizing the need for consideration of alternative conductor types or loss-reduction strategies to improve overall transmission efficiency.